Overview of the levels of ICT and information literacy skills in Canadas preservice teachers - Karsenti, Thierry; Collin, Simon; Dumouchel, Gabriel (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
To better understand the strong relationship between ICT and information literacy competencies, this short paper first describes their roles in the various education levels in Canada, including initial teacher training. We then provide an overview of empirical studies on the levels of ICT and information literacy competencies in Canadas preservice teachers and offer explanations for these levels. We conclude by proposing solutions to improve the situation, notably through effective approaches to training Canadas future teachers in ICT and information literacy competencies.